Opportunities to implement Software Defined Radio in network sensors (2017)
This paper reviews the concepts and characteristics of Software Defined Radio (SDR), focusing on the problematics of the wireless sensor networks in their fields of application; this with the purpose of finding opportunities to implement SDR functionalities to solve the requirements within the environment of a wireless sensor network.